HAS BOOK HISTORY A FUTURE? - ELIOT, SIMON (Knygotyra, 2010)
Institute of English Studies, University of LondonRoom 239, Senate House, Malet Street WC1E 7HU, UKE-mail: simon.eliot@sas.ac.uk Book history is already a large subject, but it will need to expand still further if it is to survive and flourish. In particular, we need to know more about how, in the past, information was transmitted from place to place and from period to period. We shall need to know about how roads functioned. We shall need to know much more about inland waterways and coastal trade, and about transoceanic routes. The development of postal, banking and credit systems must be studied, as must the development of national and later international telegraphic systems. New forms of information transmission introduced in the last two centuries, such as photography, the telephone, cinema, radio, television, video and the web, need to be better understood. All this requires that we view book history in a much broader context, i. e. as part of the history of communication. The integration of the history of the book and of communication will ensure that the subject will be large enough to be internally consistent, and that it will be too large and too important ever to suffer the fate of smaller and less relevant disciplines.
Keywords: book history; communication; text; information; transport